How do children learn ? - Virginia Association for Retarded Citizen, Inc.; Central Virginia Educational Television; Virginia Commonwealth University (Columbus, Ohio : Charles E. Merrill Pub. Co., 1976)
Deals with the various ways in which all children acquire knowledge, skills, and attitudes, and examines barriers to learning, and readiness for learning . Concepts distinguish between normal children and children with develomental disabilities in regard to expectancies, rate of skill acquisition, and degrees of competency in achievement of developmental tasks
Keywords: Handicapped children -- Education; Developmentally disabled children